Clinical significance of adiponectin expression in colon cancer patients - Canhoroz, Mustafa; Kanat, Ozkan; Saraydaroglu, Ozlem; Buluc, Emine; Avci, Nilufer; Cubukcu, Erdem; Manavoglu, Osman (Wolters Kluwer Medknow Publications, 2014)
Purpose: Surgery is the definitive treatment for early colon cancers. Adjuvant therapies are used with the aim of eradicating micrometastases and improving cure rates. Recent studies have proposed that adiponectin might be responsible for obesity-related malignancies. We investigated the prognostic value of this cytokine. Materials and Methods: Patients who underwent surgical removal of stage II or III (TNM staging) primary tumors and were followed for at least three years were included in the study given adequate specimen for immunohistochemical evaluation. Based on these criteria, 53 patients were included. Results: Mean age was 58.3 +/- 10.1 years (35-78 years). The mean follow-up time was 41 months (10-96 months). Immunohistochemical evaluation identified 21 patients (39.6%) with cytoplasmic adiponectin present in their specimens. The rates of recurrence were 42.9% (9/21) and 34.4% (11/32) in patients with and without adiponectin expression, respectively. In cases with adiponectin expression, mean disease - free survival was 60.3 +/- 9.03 months, and in cases without adiponectin expression, mean disease -free survival was 68.7 +/- 6.67 months (P = 0.414). Mean overall survival of patients with adiponectin expression was 65 months compared to 67 months for patients without (P = 0.786). Conclusion: Adiponectin, which is secreted by adipose tissue, may have a role in the development and progression of cancer via its pro-apoptotic and/or anti-proliferative effects. Adiponectin expression in tumor tissues is likely to have a negative effect on disease free survival in patients with stage II/III colon cancer; however, no statistically significant effect was demonstrated.
Keywords: Adiponectin; colon cancer; obesity-related malignancies